2015
DOI: 10.1111/php.12454
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silencing Heme Biosynthesis Enzymes on 5‐Aminolevulinic Acid‐mediated Protoporphyrin IX Fluorescence and Photodynamic Therapy

Abstract: Aminolevulinic acid (ALA)-mediated protoporphyrin IX (PpIX) production is being explored for tumor fluorescence imaging and photodynamic therapy (PDT). As a prodrug, ALA is converted in heme biosynthesis pathway to PpIX with fluorescent and photosensitizing properties. To better understand the role of heme biosynthesis enzymes in ALA-mediated PpIX fluorescence and PDT efficacy, we used lentiviral shRNA to silence the expression of porphobilinogen synthase (PBGS), porphobilinogen deaminase (PBGD) and ferrochela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
(26 reference statements)
2
24
0
Order By: Relevance
“…ALAD and PBGD were also decreased, but those enzymes are expected to be less rate-limiting than CPO and FC which lie immediately upstream and downstream relative to PpIX in the heme pathway. Our results broadly agree with other studies performed by various groups using a gene-silencing approach, which amply demonstrated that downregulation of ALAD or PBGD reduced the PpIX levels, but silencing of FC was the only approach that elevated PpIX levels in target cells (3133). …”
Section: Discussionsupporting
confidence: 92%
“…ALAD and PBGD were also decreased, but those enzymes are expected to be less rate-limiting than CPO and FC which lie immediately upstream and downstream relative to PpIX in the heme pathway. Our results broadly agree with other studies performed by various groups using a gene-silencing approach, which amply demonstrated that downregulation of ALAD or PBGD reduced the PpIX levels, but silencing of FC was the only approach that elevated PpIX levels in target cells (3133). …”
Section: Discussionsupporting
confidence: 92%
“…Cell suspensions were centrifuged and cell pellets were re-suspended in PBS for PpIX or Pha measurement. PpIX or Pha fluorescence was measured with a FACSCalibur flow cytometer (BD Biosciences) in the FL3 channel (488 nm excitation, 650 nm long-pass emission), which captured the second emission band of PpIX 30 . About 20,000 cells were measured and recorded for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been observed that differences in the accumulation of PpIX in healthy cells and malignant cells are due to differences in the activity of enzymes in the haem biosynthetic pathway such as porphobilinogen deaminase and ferrochelatase. 51 Molecules such as 2-allyl-2-isopropylacetamide are known to stimulate ALA synthase and ALA dehydratase activities, 52 while molecules that inhibit protoporphyrinogen oxidase 53 or upregulate coproporphyrinogen oxidase 54 have been identified which show positive results in ALA-PDT. While this highlights the potential for targeting various steps in the heme cycle in order to enhance intracellular PpIX production most attention has been paid to targeting the insertion of ferrous iron (Fe 2+ ) into the PpIX core, which is catalysed by ferrochelatase in the last step of heme biosynthesis.…”
Section: Modulators Of the Heme Pathway: Iron Chelatorsmentioning
confidence: 99%